Development of Physical Education in Elementary Schools in Bima District - Arifushalat; Sukiri; Nofi Marlina Siregar (UNIVERSITAS NEGERI JAKARTA POSTGRADUATE OF PHYSICAL EDUCATION DEPARTMENTS, 2023)
The objectives of this research are 1. To determine the development of physical education in elementary schools in Langgudu District, Bima Regency in terms of a) Physical education facilities, b) Physical education infrastructure, c) Sports human resources, d) Student participation, e) Physical fitness, 2. To find out the physical education development index in elementary schools in Bima Regency. This study uses a survey method and a quantitative approach. The population in study were students of SDN accredited A, students of SDN accredited, SDN students accredited. The sample are 216 students, 72 students for each accreditation. The sampling technique used a cluster sampling technique with stratified random sampling. Data analysis techniques use Sports Development Index (SDI) analysis. Based on the results of the research reviewed from a) Physical education facilities obtained an index value of 0.206 in the low/low category, b) Physical education infrastructure obtained an index value of 0.716 in the medium/sufficient category, c) Sports human resources obtained an index value of 0.402 in the low category/ lacking, d) Student participation obtained an index value of 0.124 in the low/less category, e) Physical fitness obtained an index value of 0.736 in the medium/adequate category. The physical education development index in elementary schools in Langgudu District, Bima Regency obtained an index value of 0.546 which is included in the medium category